Effect of self surrender practice on insulin resistance in individuals withtype 2 diabetes mellitus without depression: asingle-blinded randomized controlled trial - Siswanto, Agus; Juffrie, Muhammad; Rianto, Bambang Udji Djoko; Asdie, H.A.H (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Self surrender practice (latihanpasrahdiri/LPD) is a form of relaxation therapy that has been increasingly used, not only in the treatment of psychosomatic diseases, but also of other non-psychosomatic diseases. Previous studies reported thatSSP shows modest improvement on clinical parameters of type 2diabetes mellitus(T2DM) patients,not onlydepression symptoms improvement, but also glycemic control.However, the effect of LPD on insulin resistance has not been investigated. The study aimed to investigate the effect of LPD on insulin resistance in T2DM patients without depression. This was a single-blinded, randomized, controlledtrial conducted in outpatient unit of the Department of Internal Medicine, Dr. Soeradji Tirtonegoro General Hospital, Klaten, Central Java.The subjects of the study were T2DM patients aged over 30 yearsand had no depression.Fourthy-four T2DM patients were randomized into two groups as the controlgroup and the treatment group who underwent SSP group for eight weeks. The data of insulin resistancemeasured by HOMA-IR, perceived stress scale (PSS), fasting plasma glucose (FBG), HbA1c, and two hour plasma glucose (PPG)levels of both groups werecollected and statistically analysed.No significantly different in the patient’scharacteristics of both groups was observed.At the end of the study period, the LPD group showed reduction of HOMA-IR and HbA1c but not statistically significant, (ΔHOMA-IR = -0.39±1.52; p = 0.976; HbA1c=-0.55±0.85%; p = 0.189). The FBG and PPGincreased in the LPD group compared to control but also not statistically significant (ΔFBG=10.16±50.33; p=0.294; PPG=40.74±69.35; p=0.062). We also observed the decrease of stress level in LPD group compared to control groupbut it was no statistical significance (ΔPSS=-5.09±6.47; p=0.655).Self surrender practice (LPD) decreasesHOMA-IR, improves glycemic control (HbA1c) and reduces stress levels in T2DM patients without depressionAlthough the theyarenot statisticallysignificant, however they may be clinically significant.